Chemical properties and antioxidant activity of a water-soluble polysaccharide from Dendrobium officinale - Luo, Qiu-lian; Tang, Zhuan-hui; Zhang, Xue-feng; Zhong, Yong-hong; Yao, Su-zhi; Wang, Li-sheng; Lin, Cui-wu; Luo, Xuan (International journal of biological macromolecules, 2016)
•Structural characterization of Dendrobium officinale polysaccharide.•Mannose and glucose are the main constituent.•The polysaccharide possesses antioxidant property. In this report, a water-soluble polysaccharide was obtained from the dried stems of Dendrobium officinale Kimura et Migo by hot-water (70–75°C) extraction and 85% ethanol precipitation, and successively purification by DEAE-cellulose anion-exchange chromatography and gel-permeation chromatography. The D. officinale polysaccharide (DOP) has a molecular weight of 8500Da. Monosaccharide composition analysis reveals that DOP is composed of mannose, glucose, and arabinose with a trace of galacturonic acid in a molar ratio of 6.2:2.3:2.1:0.1. Periodate oxidation–smith degradation and 1D and 2D NMR spectroscopy analysis suggest the predominance of mannose and glucose, and it contains a 2-O-acetylglucomannan and (1→4)-linked-β-d-mannopyranosyl and (1→4)-linked-β-d-glucopyranosyl residues. Atomic force microscope shows that DOP mainly exists as rod-shaped chains, supporting high degrees of polymerization. The antioxidant activities of the polysaccharide in vitro assay indicate that DOP has good scavenging activity of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, higher scavenging activity of hydroxyl radical, and metal chelating activities.